Quality of Life in Parents of Children With Biliary Atresia. Issue 5 (November 2020) - Rodijk, Lyan H.; Schins, Eke M.W.; Witvliet, Marieke J.; Alizadeh, Behrooz Z.; Verkade, Henkjan J.; de Kleine, Ruben H.; Hulscher, Jan B.F.; Bruggink, Janneke L.M.
ABSTRACT: Objectives: The aim of the study was to determine quality of life (QoL), stress, and anxiety levels in parents of children with biliary atresia (BA), and to assess factors associated with parental QoL. Methods: Parents of children (6–16 years) with BA were included in this cross-sectional study. We used validated questionnaires to assess parental QoL, stress, and anxiety levels. We compared the results with reference data from the general population and determined associated factors using generalized linear mixed model analysis. Results are given as mean ± SD or median [min-max]. Results: We included 61 parents of 39 children (aged 11 ± 3 years). Thirty-one children (79%) had undergone a liver transplantation (LTx). Parents reported reduced family activities (88 [8–100] vs 95 [30–100], P  = 0.002) and more emotional worry (83 [17–100] vs 92 [95–100], P  < 0.001) compared with reference data, but a stronger family cohesion (85 [30–100] vs 60 [30–100], P  = 0.05). Scores on parental QoL, anxiety and stress were similar to reference data. Fathers (16.0 [11–19]) and mothers (15.4 ± 1.4) scored higher on the psychological domain compared with reference data (vs 14.7 ± 2.2, P  < 0.01). There was no significant difference in QoL of parents with children with native liver or those who had undergone LTx. Older age and high anxiety trait in parents were adversely associated with physical QoL. Household income below [Euro sign]35 000/year and high anxiety trait were adversely associated with environmental QoL. Conclusions: QoL in parents of school-aged children with BA appears to be unaffected. Parents with high-anxiety personality trait, older age, and low household income are at increased risk of impaired QoL.